Presentation And Function Of The Javanese Song For The Choir In Eucharist Ceremony At St. Maria Fatima Banyumanik Semarang (Jurnal Seni Musik, 2020)
Eucharistic celebrations that use Javanese language are very rarely carried out in the Catholic church, thereby causing a lack of public knowledge, especially people about Javanese Eucharist. This research was conducted aiming to provide information and knowledge to the public about the form and presentation of the Javanese song for the choir used to accompany the celebration of the Javanese eucharist held at the church St. Maria Fatima Banyumanik Semarang. This descriptive - qualitative research took place at St. Maria Fatima Banyumanik Semarang on May 26 and June 30, 2019 with a priest, choir officer and church members as research subjects. Data collection techniques in this study include observation, interviews and document studies. The data analysis technique used is interactive analysis. The results of the study revealed that the form of Javanese liturgical song presentation was used to accompany the celebration of the Javanese eucharist at the Church of St. Maria Fatima Banyumanik Semarang is the same as the form of presentation of the liturgical celebration of the Eucharist in general, in the form of a choir group, and the function of the use of Javanese liturgical songs in the celebration of the eucharist is as a means of communication and as a continuous contribution and cultural stability. Hopefully in the future the church will more intensively inform the celebration of the Javanese eucharist to the people, and hopefully the choir in charge can prepare song texts for the people, so as to increase the readiness and enthusiasm of the people in participating in the celebration of the Javanese eucharist at St. Maria Fatima Banyumanik Semarang.